2017
DOI: 10.1177/1534735417692097
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on the Anti-inflammatory Effects of Fucoidan in Relation to Quality of Life in Advanced Cancer Patients

Abstract: Background. Conventional anticancer therapies still cause difficulties with selective eradication and accompanying side effects that reduce patients’ quality of life (QOL). Fucoidan is extracted from seaweeds and has already exhibited broad bioactivities, including anticancer and anti-inflammatory properties, in basic studies. It is expected to enhance therapeutic efficacy and minimize side effects in cancer patients; however, despite its potential benefits, there are very few clinical trials using fucoidans. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 44 publications
1
59
1
2
Order By: Relevance
“…Besides fucose, fucoidan from S. japonica also contains minor galactose, mannose, glucose, rhamnose, and xylose. Fucoidans have been reported to have diverse bioactivities, such as antioxidant [14], anti-inflammatory [15], reno-protective [8], antitumor [16], and anticoagulant [17] activities. The molecular weight has been demonstrated to play an important role in the biological activities of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Besides fucose, fucoidan from S. japonica also contains minor galactose, mannose, glucose, rhamnose, and xylose. Fucoidans have been reported to have diverse bioactivities, such as antioxidant [14], anti-inflammatory [15], reno-protective [8], antitumor [16], and anticoagulant [17] activities. The molecular weight has been demonstrated to play an important role in the biological activities of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to assess the effect of chemotherapeutic regimens on circulating levels of fucoidan and NK cells activity. In addition, the ability of fucoidan as an adjunct therapy during conventional chemotherapy has been reported by a few investigators (12,13); therefore, the advantage of fucoidan as a supplemental therapy in the management of cancer patients is needed to be certified in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This may have affected the statistical analysis; therefore, further studies are needed to confirm the potential effects of fucoidan on NK cell activity using a large number of subjects. The proinflammatory cytokines, including interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α) were reported to be reduced after fucoidan ingestion (13). Since cancer and inflammatory responses are closely associated, we need to assess the relationship between inflammatory markers and levels of fucoidan and NK cells/immunoglobulins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies tried to investigate fucoidans molecular mechanisms in relation to their chemical structure and physicochemical properties. Therefore, different hypotheses were suggested for each activity, such as anti-tumor [31,[38][39][40], anti-coagulant [41,42], anti-viral [43,44] and anti-inflammatory activity [45,46]. These investigations revealed that various factors are relevant, such as molecular weight, sulfation pattern, sulfate content and monomeric composition [47][48][49].…”
mentioning
confidence: 99%